1998
DOI: 10.1016/s0899-3289(99)00003-6
|View full text |Cite
|
Sign up to set email alerts
|

Community reinforcement and family training (CRAFT): engaging unmotivated drug users in treatment

Abstract: Although motivation for drug abuse treatment is a substantial problem, unilateral intervention through concerned significant others (CSOs) represents a promising method for engaging unmotivated individuals. The Community Reinforcement and Family Training (CRAFT) program, based on principles of reinforcement, was developed for this specific purpose. In Phase I, CSOs received the CRAFT intervention, whereby they were taught skills for modifying a loved one's drug-using behavior and for enhancing treatment engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
3
10

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 44 publications
6
149
3
10
Order By: Relevance
“…One promising approach for engaging treatment-elusive youth is the CRAFT intervention, a unilateral family treatment approach specifically designed to aid family members or concerned significant others (CSOs) in modifying the behavior of initially unmotivated adult drug and alcohol abusers and engaging them in treatment (Kirby et al, 1999;Meyers et al, 1999;Miller et al, 1999). CRAFT, recommended in recent reviews of the engagement literature Stanton & Heath, 2004), is an outgrowth of work by Azrin and his colleagues (Azrin, Sisson, Meyers, & Godley, 1982;Sisson & Azrin, 1986) and later adapted by Meyers and Miller and their colleagues Miller et al, 1999) for use with adult substance users refusing treatment.…”
Section: Community Reinforcement and Family Training (Craft)mentioning
confidence: 99%
See 1 more Smart Citation
“…One promising approach for engaging treatment-elusive youth is the CRAFT intervention, a unilateral family treatment approach specifically designed to aid family members or concerned significant others (CSOs) in modifying the behavior of initially unmotivated adult drug and alcohol abusers and engaging them in treatment (Kirby et al, 1999;Meyers et al, 1999;Miller et al, 1999). CRAFT, recommended in recent reviews of the engagement literature Stanton & Heath, 2004), is an outgrowth of work by Azrin and his colleagues (Azrin, Sisson, Meyers, & Godley, 1982;Sisson & Azrin, 1986) and later adapted by Meyers and Miller and their colleagues Miller et al, 1999) for use with adult substance users refusing treatment.…”
Section: Community Reinforcement and Family Training (Craft)mentioning
confidence: 99%
“…A number of adult studies have demonstrated the potential of the family as a route for engaging treatment-resistant individuals with substance abuse or dependence (Garrett et al, 1997;Kirby, Marlowe, Festinger, Garvey, & LaMonaca, 1999;Marlowe, Merikle, Kirby, Festinger, & McLellan, 2001;Meyers, Miller, Hill, & Tonigan, 1999;. According to Marlowe et al (1996), substance abusers reported that family members exerted substantially more influence over their decision to enter treatment than other sources of influence, including legal pressures exerted by court-mandated treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The uncontrolled pilot project (N = 62) demonstrated a 74% IP engagement rate for CRAFT-trained CSOs (Meyers, Miller, Hill, & Tonigan, 1999). A study by Kirby and colleagues randomly assigned 32 CSOs either to CRAFT or a 12-step intervention (Kirby et al, 1999).…”
Section: Craft With Substance-dependent Clientsmentioning
confidence: 99%
“…Results showed the effectiveness of the two methods in improving the quality of life but both CRAFT and Nar-Anon were not effective in reducing the depression of family members of substance abusers This is consistent with the results of the improving the quality of life and inconsistent with the studies by Christo and Sutton (1994), Meyers et al (1998), Miller et al (1999, Richter et al (2000), Gilachen (2006) and Kanz (2009). They showed that people who participated in CRAFT and Nar-Anon showed higher interest in life and decreased depression, anxiety, hostility, improved physical and mental health compared to those who did not participate.…”
Section: Discussionmentioning
confidence: 64%